Evaluation of resource recovery through a Waste-to-Energy plant operating with municipal solid waste. (7th April 2010) - Roper, William E.; Newby, Carl
On 1 December 1984, an inter-local joint enterprise agreement was entered into between the Alexandria Sanitation Authority and the Arlington Solid Waste Authority (the 'Authorities'). The Joint Enterprise was formed to design, construct, equip, test and operate a solid waste to energy facility having an installed capacity of 975 tons per day of mixed Municipal Solid Waste (MSW). Alexandria/Arlington plant has had high availability rates (92?96%); the last three years. The Alexandria/Arlington plant also produces enough electricity to power the plant itself and over 20, 000 homes. The use of a Waste to Energy disposal system coupled with strong recycling programs has resulted in positive environmental impacts compared to traditional landfill disposal. It also has resulted in significant electrical energy generation.